Outcome of COVID-19 in patients with rheumatic and inflammatory diseases treated with mycophenolic acid: data from the French RMD COVID-19 cohort. Issue 2 (16th September 2022) - Truchetet, Marie-Elise; Drumez, Elodie; Barnetche, Thomas; Martin, Claire; Devaux, Mathilde; Goulenok, Tiphaine; Maria, Alexandre; Schmidt, Jean; Abdallah, Nassim Ait; Melki, Isabelle; Hachulla, Eric; Richez, Christophe
Abstract : Background: Patients with inflammatory rheumatic and musculoskeletal diseases (iRMD) receiving mycophenolic acid (MPA) may have a less favourable outcome from COVID-19 infection. Our aim was to investigate whether MPA treatment is associated with severe infection and/or death. Methods: IRMD patients with and without MPA treatment with highly suspected/confirmed COVID-19 were included in this observational multicentre study. The primary outcome was death rate from COVID-19 with secondary objectives to determine the severity of infection and length of hospital stay. Outcome comparisons were made using regression models with and without adjustment on prespecified confounding factors. ORs, sub-HR (sHR) and 95% CIs were calculated using patients not treated with MPA as a reference group. Results: Of the 1977 patients, 1928 were not treated with MPA (393 were MPA eligible), and 49 patients were treated with MPA. MPA-treated patients had more severe disease, longer hospital stays and higher death rate from COVID-19 than non-MPA patients (OR 8.02 (95% CI 3.35 to 19.20), p<0.001; sHR 0.57 (95% CI 0.33 to 0.98), p=0.040; OR 11.58 (95% CI 4.10 to 32.69), p<0.001). In adjusted analyses, however, no outcome was independently associated with MPA treatment. Death rate, severity and length of hospital stay of MPA-treated patients were not significantly different from those of not treated but MPA-eligible patients. Conclusion: MPA therapy is not associated with a more severe COVID-19 infection. However, due to increased vulnerability of developing a severe form of COVID-19, careful consideration should be taken with iRMD patients likely to be treated with MPA. Trial registration number: NCT04353609 .